a) $(x + y + z)(x + y - z)$ = $((x+y)+z)((x+y)-z) = (x+y)^2 - z^2 = x^2 + 2xy + y^2 - z^2$
б) $(x - y)(x + y) = x^2 - y^2$
в) $(x - y + z)(x + y + z) = ((x+z)-y)((x+z)+y)=(x+z)^2 - y^2 = x^2+2xz+z^2-y^2$
г) $(x - y - z)(x + y + z) = (x-(y+z))(x+(y+z)) = x^2-(y+z)^2 = x^2 - (y^2 + 2yz+z^2) = x^2 - y^2 - 2yz - z^2$
д) $(x - y - z)(x + y + z) = x^2 - y^2 - 2yz - z^2$
e) $(-x - y - z)(x + y + z) = -(x+y+z)(x+y+z) = -(x+y+z)^2=-(x^2+y^2+z^2+2xy+2xz+2yz)=-x^2 - y^2 - z^2 - 2xy - 2xz - 2yz$
Ответы:
a) $x^2 + 2xy + y^2 - z^2$
б) $x^2 - y^2$
в) $x^2 + 2xz + z^2 - y^2$
г) $x^2 - y^2 - 2yz - z^2$
д) $x^2 - y^2 - 2yz - z^2$
e) $-x^2 - y^2 - z^2 - 2xy - 2xz - 2yz$